Divergent Allometric Trajectories in Gene Expression and Coexpression Produce Species Differences in Sympatrically Speciating Midas Cichlid Fish. (24th May 2019) - Fruciano, Carmelo; Meyer, Axel; Franchini, Paolo
Abstract: The mechanisms of speciation without geographic isolation (i.e., sympatric speciation) remain debated. This is due in part to the fact that the genomic landscape that could promote or hinder species divergence in the presence of gene flow is still largely unknown. However, intensive research is now centered on understanding the genetic architecture of adaptive traits associated with this process as well as how gene expression might affect these traits. Here, using RNA-Seq data, we investigated gene expression of sympatrically speciating benthic and limnetic Neotropical cichlid fishes at two developmental stages. First, we identified groups of coexpressed genes (modules) at each stage. Although there are a few large and well-preserved modules, most of the other modules are not preserved across life stages. Second, we show that later in development more and larger coexpression modules are associated with divergence between benthic and limnetic fish compared with the earlier life stage. This divergence between benthic and limnetic fish in coexpression mirrors divergence in overall expression between benthic and limnetic fish, which is more pronounced later in life. Our results reveal that already at 1-day posthatch benthic and limnetic fish diverge in (co)expression, and that this divergence becomes more substantial when fish are free-swimming but still unlikely to have divergent swimming and feeding habits. More importantly, our study describes how the coexpression of several genes through development, as opposed to individual genes, is associated with benthic–limnetic species differences, and how two morphogenetic trajectories diverge as fish grow older.